A PROPOSAL FOR SOP DESIGN AND COMMUNICATION TRAINING MATERIAL INFORMED BY RESEARCH ON REAL BUSINESS ENCOUNTER - Kadek Ratih Dwi Oktarini (Journal of Applied Sciences in Travel and Hospitality, 2019)
The current study reports on an attempt to implement some results from a previous study on natural conversation as a Part of Standard Operating Procedure (SOP) and Communication Training Material for Face to Face Communication in Service Industry. The specific research on natural conversation is Oktarini (2016). That study analyzed a heated complaint sequence of interaction (complaint sequence-in short) between a hotel staff and a guest using Conversation Analysis (CA) (Have, 2007; Sidnell, 2010). It appeared that some of the actions of the hotel staff result in more preferable responses than the others. In terms of resolving the complaint sequence amicably, any actions that lead to calmer guest or formulation of problem, are deemed to be preferred. The current study specifically attempts to, firstly capture the moment by moment of small actions (nudges) (Cf. The Royal Institution, 2015) of the staff that garners preferable responses and vice versa; and secondly, translate those “nudges” as a component of SOP design and Communication Training Material. The framework use to translate staff’s actions into SOP design and training material is Conversation Analysis Role-play Method or CARM (Stokoe, 2014, 2018).